Development of partially defatted peanuts - Sarmiento Judith S.
Shelled, raw peanuts, grade as '4a' in the market were hydraulically pressed to remove the oil and produce a partially defatted peanut product. Moisture and fat content of the raw peanuts were determined to be 5.33% and 45.62%, respectively. The optimum time for oil removl was found to be 60 minutes. Objective and subjective test results showed that optimum time-temperature combinations for roasting was 150°C for 3.5 minutes. The optimum level of salt to be added to the water used to reshape the nuts was found to be 4% while the optimum level of garlic powder was 2%. General acceptability of the final product was found to improve upon addition of MSG and salt coating. Proximate analysis was done on the final product. Fat content was found to be 31.83%. Moisture was 2.0% and protein content was 30.88%. Lastly, two commercial brands of greaseless peanuts were analyzed for fat content. Brand A was found to containa fat content of 45.58% while Brand B has 52.18%.